1989
DOI: 10.1002/ijc.2910430316
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility antigens in primary and metastatic squamous cell carcinoma of the larynx

Abstract: A series of 38 primary laryngeal and hypopharyngeal tumours, 15 lymph-node metastases and normal tissue were evaluated in frozen sections for the expression of MHC class I and II antigens, using monomorphic monoclonal antibodies (MAbs) to HLA-ABC, beta 2-microglobulin, DR, DP, DQ, HLA-B and polymorphic HLA-ABC antigens. Normal distant mucosa of larynx reacted to anti-class I antibodies but not to anti-class II. In 9 primary tumours (23.7%) HLA class I antigens were not observed. The remaining 29 showed a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 50 publications
(36 reference statements)
4
53
1
Order By: Relevance
“…This is in agreement with results reported by David & Kevin (10) and Sakai et al (15). In human tumors, the expression of HLA-DR antigen has been reported to be associated with histological degree of cell differentiation (8,9,16). In the present study, the differentiated-type gastric carcinomas expressed HLA-DR antigen more frequently than undifferentiated-type carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with results reported by David & Kevin (10) and Sakai et al (15). In human tumors, the expression of HLA-DR antigen has been reported to be associated with histological degree of cell differentiation (8,9,16). In the present study, the differentiated-type gastric carcinomas expressed HLA-DR antigen more frequently than undifferentiated-type carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…be associated with well-differentiated states of the tumor cells, and the tumors with HLA-DR antigen expression have a good prognosis (8,9).…”
mentioning
confidence: 99%
“…Such down-regulation would supply a selective growth advantage for malignant tumours by allowing neoplastic cells to escape CTL-mediated destruction. Indeed when class I MHC expression is lost in breast (Concha et al, 1991) or laryngeal (Esteban et al, 1989) carcinomas, a significantly poorer clinical outcome is found.…”
mentioning
confidence: 99%
“…The class I MHC molecule consists of three alpha regimes, covalently linked to beta-2-microglobulin (beta 2m), which are encoded by separate genes, and linked prior to expression at the cell membrane (Ploegh et al, 1981;Arce-Gomez, 1978 (Eisenbach et al, 1983;1985). Studies on the expression of human MHC class I antigens in primary vs metastatic tumour are limited; for example malignant melanoma, digestive tract, and laryngeal tumours (Ruiz-Cabello et al, 1989;Esteban et al, 1989). In these studies, both increased and decreased expression of monomorphic determinants of HLA class I was observed in the metastases compared with their primaries.…”
mentioning
confidence: 99%
“…With these immunogenic tumours, those with a high level of MHC antigen expression show low metastatic ability; transfection and subsequent expression of the H2K gene into otherwise highly metastatic H2K-negative tumour cell variants reduces tumour growth, and prevents metastasis (Eisenbach et al, 1983;1985). Studies on the expression of human MHC class I antigens in primary vs metastatic tumour are limited; for example malignant melanoma, digestive tract, and laryngeal tumours (Ruiz-Cabello et al, 1989;Esteban et al, 1989). In these studies, both increased and decreased expression of monomorphic determinants of HLA class I was observed in the metastases compared with their primaries.…”
mentioning
confidence: 99%